Proven COVID‐19—associated pulmonary aspergillosis in patients with severe respiratory failure. Issue 10 (4th July 2021) - Fortarezza, Francesco; Boscolo, Annalisa; Pezzuto, Federica; Lunardi, Francesca; Jesús Acosta, Manuel; Giraudo, Chiara; Del Vecchio, Claudia; Sella, Nicolò; Tiberio, Ivo; Godi, Ilaria; Cattelan, Annamaria; Vedovelli, Luca; et al.
Abstract: Background: An increasing number of reports have described the COVID‐19–associated pulmonary aspergillosis (CAPA) as being a further contributing factor to mortality. Based on a recent consensus statement supported by international medical mycology societies, it has been proposed to define CAPA as possible, probable, or proven on the basis of sample validity and thus diagnostic certainty. Considering current challenges associated with proven diagnoses, there is pressing need to study the epidemiology of proven CAPA. Methods: We report the incidence of histologically diagnosed CAPA in a series of 45 consecutive COVID‐19 laboratory‐confirmed autopsies, performed at Padova University Hospital during the first and second wave of the pandemic. Clinical data, laboratory data and radiological features were also collected for each case. Results: Proven CAPA was detected in 9 (20%) cases, mainly in the second wave of the pandemic (7/17 vs. 2/28 of the first wave). The population of CAPA patients consisted of seven males and two females, with a median age of 74 years. Seven patients were admitted to the intensive care unit. All patients had at least two comorbidities, and concomitant lung diseases were detected in three cases. Conclusion: We found a high frequency of proven CAPA among patients with severe COVID‐19 thus confirming at least in part the alarming epidemiological data of this important complication recently reported as probable CAPA.